Revisiting Unemployment in Indonesia: Error Correction Model (ECM) Analysis - Widyarta, I Kadek Purna; Samosir, Cecilia Putri Dianti; Aysyah, Putri; Kartiasih, Fitri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
The rise in population in Indonesia has led to the emergence of a very pressing problem, namely the unemployment rate. Indonesia is currently ranked second in ASEAN as the country with the highest unemployment rate. It has become a serious problem due to the negative impact of such increases in crime, declining economic output, increasing poverty, rising numbers of demonstrators, and rising death rates, especially the rise in suicide rates among men. The rise in unemployment is caused by many factors, one of which is the economy. Some economic variables will experience a high rise in the next few years to ensure the impact tested using the Error Correction Model (ECM) method. This study looks at the influence of macroeconomic variables such as foreign direct investment, PDB, government expenditure, exchange rates, and imports on the unemployment rate in Indonesia from 1986 to 2022. The results show that there is both long-term and short-term influence, with the variable that has the most significant influence being foreign direct investments. It needs the attention of the government in determining policies and handling them to address the problem of unemployment in Indonesia.